2013
DOI: 10.5935/abc.20130241
|View full text |Cite
|
Sign up to set email alerts
|

Value of Coronary Artery Calcium Score to Predict Severity or Complexity of Coronary Artery Disease

Abstract: Background Prediction of severity or complexity of coronary artery disease (CAD) is valuable owing to increased risk for cardiovascular events. Although the association between total coronary artery calcium (CAC) score and severity of CAD, Gensini score was not used, it has been previously demonstrated. There is no information about the association between total CAC score and complexity of CAD. ObjectivesTo investigate the association between severity or complexity of coronary artery disease (CAD) assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
1
9
2
Order By: Relevance
“…Data from migrant Indian Asian populations show little difference in coronary calcium scores in men between Asians and Caucasians in the USA . This study was conducted before coronary artery calcium score measurement became routine and used a semi‐quantitative measure of CAD atheroma burden (Gensini score) that shows a weak correlation ( r = 0.30) with coronary calcium scores . However, in general calcium scores correlate with severity of atheromatous disease measured on CT coronary angiography in Pakistani populations suggesting that this relationship is still relevant to modern practice.…”
Section: Discussionmentioning
confidence: 96%
“…Data from migrant Indian Asian populations show little difference in coronary calcium scores in men between Asians and Caucasians in the USA . This study was conducted before coronary artery calcium score measurement became routine and used a semi‐quantitative measure of CAD atheroma burden (Gensini score) that shows a weak correlation ( r = 0.30) with coronary calcium scores . However, in general calcium scores correlate with severity of atheromatous disease measured on CT coronary angiography in Pakistani populations suggesting that this relationship is still relevant to modern practice.…”
Section: Discussionmentioning
confidence: 96%
“…A study done by Gökdeniz et al indicated that cut-off value of CAC greater than 809 with sensitivity of 67.6% and specificity of 87.6% could be used to predict high SYNTAX score in patients [ 13 ]. However, in our study, the cut-off of the total CAC score in predicting patients with SYNTAX score of >27 was 212 (AUC = 0.743, 95% CI = 0.589-0.896, p = 0.007).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between CAC score and its quantification of future cardiac events has been demonstrated. Some studies have shown an association of CAC score with angiographically proven CAD [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calcium score based on the Agatston method was defined as the presence of a lesion with an area greater than 1 mm 2 , and peak intensity greater than 130 Hounsfield Units, which was automatically identified and marked with color by the software. All lesions were added to calculate the total calcium score with the Agatston method [ 22 ].…”
Section: Methodsmentioning
confidence: 99%